Widespread structural variations in the human genome - Lee, Charles (Henry Stewart Talks, 2007)
Genetic differences and similarities between normal individuals, Single Nucleotide Polymorphisms (SNPs), Structural variants in the human genome, Comparative Genomic Hybridization (CGH), Clinical genetic diagnostics, Copy Number Variation (CNV), Overlapping, Large-scale variation, CNVs in the human genome is probably underestimated, Fine-scale structural variation of the human genome, In silico computational strategy, Holes in the human genome, Common deletion polymorphisms, International HapMap Project, Genotyping failures, Common/complex diseases, Gene expression, Implications of CNVs to genetic diagnostics, Toward a global CNV map for the human genome, Copy Number Variation Project, CNVs in other mammalian species
Archived at 2018/05/31